Proof of Kochen–Specker Theorem: Conversion of Product Rule to Sum Rule - Toh, S.P.; Zainuddin, Hishamuddin (Chinese Physical Society & IOP Publishing Ltd, 2009)
Valuation functions of observables in quantum mechanics are often expected to obey two constraints called the sum rule and product rule. However, the Kochen–Specker (KS) theorem shows that for a Hilbert space of quantum mechanics of dimension